Adsorption and desorption behavior of basic proteins on zeolites - Matsui, Masayoshi; Kiyozumi, Yoshimichi; Mizushina, Yoshiyuki; Sakaguchi, Kengo; Mizukami, Fujio (Separation and purification technology, 2015)
[Display omitted] Adsorption and desorption behavior of chymotrypsinogen A (CTRA), cytochrome c (cyt c) and lysozyme (LYZ) on potassium cation types of zeolite L (K-LTL) and ferrierite (K-FER) was investigated. K-FER with SiO2/Al2O3 ratio of 17.7 exhibited better protein adsorption ability than K-LTL with SiO2/Al2O3 ratio of 6.0. The adsorption of proteins on zeolites took place rapidly, and more than 80% of the applied proteins were adsorbed within 30min. The proteins tightly adsorb on zeolites because most of the adsorbed proteins were retained on zeolites after washings. Recovery of proteins adsorbed on zeolites was examined by using various concentrations of KCl solutions. In the presence of 1M KCl, more than 90% of CTRA and cyt c, and 100% of LYZ were recovered from K-LTL. The recovery rates of the proteins from K-FER were entirely low. This difference between the two zeolites would be due to that basic amino acid residues of the proteins electrostatically interacting with negative charges in the pores of K-FER are difficult to be exchanged with K+ cations in the KCl solution because the pores of K-FER are much smaller in size than those of K-LTL. We also confirmed that CTRA recovered from K-LTL retained 84% of the initial activity. Zeolites have the potential as the cation exchange adsorbent of proteins.